2017
DOI: 10.1177/2325967117728041
|View full text |Cite
|
Sign up to set email alerts
|

Pectoralis Minor Contracture in Throwing Shoulders of Asymptomatic Adolescent Baseball Players

Abstract: Background:Although scapular malpositioning is commonly associated with rotational deficits and risk of injury, modifiable causes of such malpositioning in overhead athletes are not well described.Purpose/Hypothesis:The purpose of this study was to examine the scapulothoracic profile of adolescent baseball players, specifically, pectoralis minor (PM) length. We hypothesized that PM would be shorter in throwing shoulders compared with nonthrowing shoulders.Study Design:Cross-sectional study; Level of evidence, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 28 publications
1
16
0
Order By: Relevance
“…Third, the reliability and validity of the scapular index have not been firmly established, although it has been used in several studies. 10 , 15 , 47 Fourth, participants in this study were recruited from a high-school baseball team. However, they had a mean experience in baseball of 8 years.…”
Section: Discussionmentioning
confidence: 99%
“…Third, the reliability and validity of the scapular index have not been firmly established, although it has been used in several studies. 10 , 15 , 47 Fourth, participants in this study were recruited from a high-school baseball team. However, they had a mean experience in baseball of 8 years.…”
Section: Discussionmentioning
confidence: 99%
“…they participated in elite sports as elite sport can cause anatomical adaptations in the gleno-humeral joint and muscles around the area (Hodgins et al 2017 ).…”
Section: Methodsmentioning
confidence: 99%
“…• they had pain in the shoulders that interfered with activities of daily living (ADLs), as pain influences the function of the scapular stabilising muscles (Moezy, Sepehrifar & Dodaran 2014); • they participated in elite sports as elite sport can cause anatomical adaptations in the gleno-humeral joint and muscles around the area (Hodgins et al 2017).…”
Section: Methodsmentioning
confidence: 99%
“…From our systematic review, a consistent pattern of increased scapular anterior tilting and internal rotation was reported in the dominant shoulders than in the nondominant shoulders of athletes who participated in overhead sports. Previous studies have shown significant loss of internal rotation range of motion (glenohumeral internal rotation deficit), 36 increased humeral retroversion, 37,38 tightness of the posterior shoulder capsule and muscles, 39,40 and tightness of pectoralis minor 41,42 in the dominant shoulders of athletes who participated in overhead sports, and these were associated with increased scapular anterior tilting and internal rotation. [43][44][45] In this connection, the glenohumeral contact pressure was significantly increased with more scapular internal rotation in a cadaveric study.…”
Section: Scapular Kinematics In Healthy Overhead Athletesmentioning
confidence: 96%